Smart Recycling Bins Segregation Automatically - NurFakhira; Norfaiza Fuad (Evolution in Electrical and Electronic Engineering, 2024)
Malaysia faces a critical waste management challenge as its landfills are near full capacity which is risking the exhaustion of space for solid waste disposal by 2050. Waste segregation is an effective strategy to reduce waste and boost recyclable numbers. This development introduces smart recycling bins that automatically segregate using an inductive proximity sensor for metal detection and an LDR sensor for identifying plastic and paper. Two servo motors execute the segregation process. The mechanical system consists of servo motors that rotate flaps which allow the trash to fall into the target receptacle. Ultrasonic sensors monitor garbage levels and then notify through Blynk and activate LEDs when bins are full. The system can operate on a 9V 2A external power supply. Results reveal an 80% accuracy for inductive proximity sensors detecting metal and a 50% accuracy for LDR sensors detecting plastic and paper. This system enables real-time monitoring through applications, enhancing management alertness for timely cleaning efforts.